National Health and Nutrition Examination Survey II, 1976-1980: Medical History Ages 6 Months-11 Years ([Verlag nicht ermittelbar], 1984)
The Health and Nutrition Examination Survey II, 1976-1980: Medical History ages 6 months-11 years contains demographic characteristics and health histories of 6,839 interviewed persons 6 months-11 years of age. The medical histories obtained include items on birth weight, birth order, sitting and walking stages, infant feeding, congenital conditions, accidental poisoning, bad accidents, hospitalizations, activity limitation, pneumonia, colds, diarrhea, pica, vision problems, chronic conditions checklists, allergies, lead poisoning, medications, kidney, bladder, and urinary tract conditions, anemia, hearing and speech, lung and chest conditions, school meal programs, and parents' height and weight.